Analisis Financial Distress Menggunakan Model Springate dan Model Grover pada PT Garuda Indonesia (Persero) Tbk Periode 2015–2024 - Nabila Amalia Nurrohmah; Agus Supriatna (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the financial distress condition of PT Garuda Indonesia (Persero) Tbk during the period 2015–2024 using the Springate and Grover models. The research employs a quantitative descriptive approach with secondary data obtained from the company’s annual financial statements. Financial distress analysis is conducted by calculating financial ratios included in each model to describe the company’s financial condition over the observation period. The results indicate that PT Garuda Indonesia (Persero) Tbk experienced financial distress during several periods, particularly before and during the COVID-19 pandemic, which was reflected in weakened liquidity, declining profitability, and reduced efficiency in asset utilization. However, following the financial restructuring process after 2021, both the Springate and Grover models show an improvement in the company’s financial condition, indicating a transition toward a more stable non-distress status. Although the Springate and Grover models use different financial indicators and classification approaches, both are able to descriptively capture the dynamics of financial distress experienced by the company. The differences in classification results reflect the distinct focus of each model, where the Springate model is more sensitive to liquidity and operational performance, while the Grover model emphasizes asset profitability. Therefore, the combined use of both models provides a more comprehensive overview of the financial distress condition of PT Garuda Indonesia (Persero) Tbk during the research period.